In Situ Monitoring of Lithium Metal Anodes and Their Solid Electrolyte Interphases by Transmission Electron Microscopy. Issue 6 (19th June 2021) - Chen, Chih-Yao; Tsuda, Tetsuya; Oshima, Yoshifumi; Kuwabata, Susumu
Abstract : Transmission Electron Microscopy Observation A sophisticated transmission electron microscopy holder with both the advantages of conventional open‐cell and liquid cell approaches is realized by Tetsuya Tsuda, Susumu Kuwabata, and co‐workers in article number 2100018 . Its usage facilitates to accurately monitor Li metal anode reactions under realistic operation conditions.